PRIMARY CHRONIC OSTEOMYELITIS OF THE JAW IN CHILDREN: TWO CASE REPORTS - A.YU. KUGUSHEV; A.B. LOPATIN; S. DAGHER (Паёми Сино, 2025)
Methods: Between 2015 and 2023, forty-five children were treated for PCO at the Department of Oral and Maxillofacial Surgery, Russian Childrens’ Clinical Hospital, affiliated with the Pirogov Russian National Research Medical University. Of these, 17 children received combination therapy involving resection with removal of all granulomatous tissue, followed by postoperative administration of denosumab. From this group, two patients – a 15-yearold boy and a 6-year-old girl – were selected for this article due to their differing anthropometric characteristics and recurrent disease course.